Organization Development and Firm Performance: A Comparison of Multinational and Local Firms - Lau, Chung-Ming; Ngo, Hang-Yue (Journal of International Business Studies, 2001)
This study examines the usage and outcomes of organization development (OD) interventions in multinational firms. We test competing hypotheses derived from the cultural and institutional/isomorphic perspectives. Data from firms operating in Hong Kong show that Western firms (U.S. and European) are more receptive to OD interventions than Asian firms (local and Japanese), which supports the cultural explanation. However, the local isomorphism explanation is valid in predicting organizational outcomes that OD interventions have similar effects regardless of a firm's country origins. Hence, neither perspective alone is sufficient to explain both usage and outcomes. This implies that local adaptation of OD interventions is a complex issue for managing multinational firms.